2014
DOI: 10.1093/mnras/stu1941
|View full text |Cite
|
Sign up to set email alerts
|

Empirical period–colour and amplitude–colour relations for Classical Cepheids and RR Lyrae variables

Abstract: We analyze Galactic, Large Magellanic Cloud and Small Magellanic Cloud Cepheids and RR Lyrae variables in terms of period-color (PC) and amplitude-color (AC) diagrams at the phases of maximum and minimum light. We compiled Galactic Cepheids V -and I-band data from the literature. We make use of optical bands light curve data from OGLE-III survey for Cepheids and RR Lyrae variables in the Magellanic Clouds. We apply the F -statistical test to check the significance of any variation in the slope of PC and AC rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

22
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(83 citation statements)
references
References 31 publications
22
60
1
Order By: Relevance
“…For RR Lyraes, Kanbur & Fernando (2005) investigated the PC and AC relations based on 4829 RR Lyraes in Large Magellanic Cloud obtained from the MACHO project, and found that the PC and AC relations at minimum light have a slope close to zero for this set of RR Lyraes. A similar result was also found with the fundamental mode RR Lyraes in the Large and Small Magellanic Cloud using the Optical Gravitational Lensing Experiment III (OGLE-III) data (Bhardwaj et al 2014). Note that the flatness of the RR Lyraes PC relation at minimum light provides an alternate approach to estimate the reddening (Sturch 1966).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…For RR Lyraes, Kanbur & Fernando (2005) investigated the PC and AC relations based on 4829 RR Lyraes in Large Magellanic Cloud obtained from the MACHO project, and found that the PC and AC relations at minimum light have a slope close to zero for this set of RR Lyraes. A similar result was also found with the fundamental mode RR Lyraes in the Large and Small Magellanic Cloud using the Optical Gravitational Lensing Experiment III (OGLE-III) data (Bhardwaj et al 2014). Note that the flatness of the RR Lyraes PC relation at minimum light provides an alternate approach to estimate the reddening (Sturch 1966).…”
Section: Introductionsupporting
confidence: 81%
“…For instance, the interaction of HIF with the photosphere at certain pulsation phases would imply that the observed PC relation will be flat or very shallow (that is, the slope of the PC relation is close to zero) at these phases (for a thorough discussion on this, see Bhardwaj et al 2014, and references therein). In the case of Cepheids, the PC and AC relations have been extensively studied in a series of papers ; Kanbur & Ngeow 2006;Kanbur et al 2007Kanbur et al , 2010, as well as in Bhardwaj et al (2014). For RR Lyraes, Kanbur & Fernando (2005) investigated the PC and AC relations based on 4829 RR Lyraes in Large Magellanic Cloud obtained from the MACHO project, and found that the PC and AC relations at minimum light have a slope close to zero for this set of RR Lyraes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for discrepancy in Cepheid-based distance estimates is the significant nonlinearities at various periods during the different phases of pulsation at optical wavelengths (Ngeow & Kanbur 2006b;Bhardwaj et al 2014). These nonlinearities are also observed for mean light P-L relations at optical bands but are expected to be less significant at NIR wavelengths (Bono et al 1999;Madore & Freedman 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Studying the period-colour relations of RRL stars using the OGLE III data (Soszyński et al 2009(Soszyński et al , 2010 of the Large and Small Magellanic Clouds (MCs), Bhardwaj et al (2014) found that the slope of the (V − I)0 versus logP relation for RRab and RRc stars are 0.093/0.055 and 0.604/0.472 in the LMC/SMC, respectively. (V − I)0 corresponds the min2 data here, measured at the phase of the light minimum.…”
Section: Minimum Colour and Temperature Valuesmentioning
confidence: 99%